Avaliação experimental do desempenho de unidades eólicas quanto à geração de distorções harmônicas - Moura, Leandro Pains (2017)
The search for alternative sources of energy, aiming the attendance of the energy matrix, has led to a vertiginous increase in the use of wind energy in Brazil and in the world, which receives strong government and private incentives, becoming an increasingly competitive and attractive source of energy. Consequently, the interaction between wind farms and connection networks shows an area of strong research interests due to the operational characteristics of these complexes, which, in consonance with the properties of the primary energy source, translate into a variability of the energy produced and in the use of electronic converters. As a result of these operational characteristics, although there is acknowledgments that the basic function of wind farms is related to the supply of active power at the fundamental frequency, the operation of these installations is linked to phenomena associated with the area of electrical energy quality, such as harmonic voltage/current distortions, which can interact and cause impacts on the electrical connection networks. Therefore, in the context of the interconnections discussed here, the subject presents itself with great challenges and, punctually, motivated the developments carried out here, which are focused on studies about the determinant factors in the injection of harmonic distortions in the electric systems, using, for that, the structural design based on synchronous generators. The works considered in this master’s dissertation contemplate activities related to the development of mathematical models, computational implementation, laboratory assemblies and performance studies, aiming, above all, to complement and validate elements of a theoretical nature already contemplated in previous researches.